Uncovering Vegetation Changes in the Urban–Rural Interface through Semi-Automatic Methods - Barbosa, Bruno (2022)
Barbosa, B., Rocha, J., Costa, H., & Caetano, M. (2022). Uncovering Vegetation Changes in the Urban–Rural Interface through Semi-Automatic Methods. Applied Sciences, 12(5), 1-14. [2294]. https://doi.org/10.3390/app12052294 -------------- Funding: This research was funded by Portuguese Foundation for Science and Technology, I.P. (FCT), under the framework of the Project “FORESTER—Data fusion of sensor networks and fire spread modelling for decision support in forest fire suppression” [name of funder] grant number PCIF/SSI/0102/2017. The APC was funded by the Research Unit UIDB/00295/2020 and UIDP/00295/2020.